Improving Chinese Reading and Writing Skills: Second Language Acquisition Theory Perspective - Menglan Luo; Jiraporn Chano; Thatchai Chittranun; Bussayarat Nithideechaiwarachok (Journal of Educational Issues, 2024)
This research aimed to study the theories and principles for improving Chinese reading and writing skills based on second language acquisition theory and investigated the factors affecting Chinese major students’ reading and writing skills for university students in northeast of Thailand. The sample groups were 386 Chinese language major students from 12 universities in the northeast of Thailand selected by voluntary selection, 9 Chinese language major students, and 3 Chinese language lecturers at universities in the northeast of Thailand selected by purposive sampling. The research instruments were questionnaires, interview form for students, and interview form for lectures. Content analysis, exploratory factor analysis, mean and standard deviation were used to analyze the collected data. The findings revealed that the appropriate theories and principles for improving reading and writing skills in Chinese as a second language were sociocultural theory, monitor theory, and contrastive analysis hypothesis. Factors affecting reading and writing skills in Chinese as a second language were vocabulary, grammar, language environment, attitude, motivation, and anxiety.